Policy Paper : Strategis Kebijakan E-Goverment pada Biro Pemerintahan dan Otonomi Daerah Provinsi Lampung - Dewi, Atria (Jurnal Administrasi Karya Dharma, 2024)
The impact of e-government on the provision of public services is quite significant, because it can produce faster, better and more efficient public services, which in turn promotes the principles of good governance. The aim of this research is to determine strategic e-government policy at the Lampung Province Regional Government and Autonomy Bureau. This research was carried out using qualitative descriptive analysis by conducting interviews with staff from the Lampung provincial government and regional autonomy bureau and observing the relevant bureau's website. The findings show that the main problems faced are the absence of experts in the IT field, no training or outreach regarding website management, as well as inadequate supporting facilities and infrastructure. Therefore, there is a need for a strategic system to realize e-government in Government Bureaus and regional autonomy in Lampung province. The solutions and suggestions given are the need for socialization, placement of IT experts, planning IT-based system guidelines, and completing the necessary facilities and infrastructure. Apart from support from the central government, there is a need to accelerate budget realization related to e-government implementation in order to create applications that are more effective, efficient, transparent and inclusive.